Multi-Modal Hallucinations and Cognitive Function in Parkinson's Disease - Katzen, Heather (S. Karger AG, 2010)
BACKGROUND/AIMS: Hallucinations have been linked to a constellation of cognitive deficits in Parkinson's disease (PD), but it is not known whether multi-modal hallucinations are associated with greater neuropsychological dysfunction. METHODS: 152 idiopathic PD patients were categorized based on the presence or absence of hallucinations and then were further subdivided into visual-only (VHonly; n = 35) or multi-modal (VHplus; n = 12) hallucination groups. All participants underwent detailed neuropsychological assessment. RESULTS: Participants with hallucinations performed more poorly on select neuropsychological measures and exhibited more mood symptoms. There were no differences between VHonly and VHplus groups. CONCLUSIONS: PD patients with multi-modal hallucinations are not at greater risk for neuropsychological impairment than those with single-modal hallucinations.